PEMBELAJARAN TAHFIDZ AL-QUR’AN PADA ANAK USIA DINI DI RA ASY-SYUHADA PURBASARI - Lubis, Reza Noprial (TA'LIM : Jurnal Studi Pendidikan Islam, 2024)
This research aims to describe the implementation of Al-Quran tahfiz learning. The implementation of learning consists of aspects of planning, learning activities, and assessment of learning outcomes for Tahfiz Al Quran Juz 30 in group B at RA Asy-Syuhada Purbasari. This type of research is descriptive. The subjects of this research included group B tahfiz teachers, the RA Asy-Syuhada school principal, and 21 group B children. The object of this research is the implementation of Al-Quran tahfiz learning in group B. Data collection techniques use observation, interviews and documentation. Data were analyzed using qualitative descriptive analysis techniques. The research results show; (1) the planning carried out by the teacher in learning Al-Quran tahfiz through unwritten planning from teacher meetings and written planning in the Daily Activity Plan, (2) implementation of Al-Quran tahfiz activities is carried out in two forms of activities, namely group activities and tasmi activities. Group activities are carried out by dividing children into two groups based on their memorization ability. The teacher dictates verses one by one to the children in a classical manner. The child listens to the teacher's reading, then imitates the teacher's reading repeatedly until the child pronounces it fluently. Tasmi activities are carried out by combining all group B children, then the teacher gives instructions to the children to repeat the letters that have been memorized individually, in groups or classically, (3) the assessment is carried out by observing the children individually when repeating the memorization using anecdotal note assessment tools and checklist.